2017
DOI: 10.1111/liv.13504
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of systemic inflammation in hepatitis B‐precipitated ACLF: Differentiate it from No‐ACLF

Abstract: Systemic inflammation in HB-ACLF was characterized by an excessive innate immune response, which was associated with disease progression and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 26 publications
1
68
1
Order By: Relevance
“…Generally, HB‐ACLF is believed to be caused by DAMP‐induced sterile inflammation . However, it may be confounded by non‐sterile inflammation, as evidenced by increased circulating microbial burden and up‐regulation of antibacterial genes in leukocytes of HB‐ACLF patients . The positive correlation between Burkholderiaceae and CXC chemokine IP‐10, which is a key chemokine‐driving SI in decompensated cirrhosis and ACLF, suggested that specific bacteria in the circulating microbiome may contribute to SI in HB‐ACLF.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Generally, HB‐ACLF is believed to be caused by DAMP‐induced sterile inflammation . However, it may be confounded by non‐sterile inflammation, as evidenced by increased circulating microbial burden and up‐regulation of antibacterial genes in leukocytes of HB‐ACLF patients . The positive correlation between Burkholderiaceae and CXC chemokine IP‐10, which is a key chemokine‐driving SI in decompensated cirrhosis and ACLF, suggested that specific bacteria in the circulating microbiome may contribute to SI in HB‐ACLF.…”
Section: Discussionmentioning
confidence: 99%
“…Systemic inflammation (SI) is a key factor driving the occurrence and progression of ACLF, irrespective of aetiology . It can be either sterile or non‐sterile in nature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HBV can cause ACLF in acute infection or in the setting of HBV reactivation in the setting of treatment cessation, HBV resistance, chemotherapy, or immunosuppression . Excess innate immune responses to viral antigens mediated by pathogen‐associated molecular patterns and damage‐associated molecular patterns (DAMPs) may play a role in the development of ACLF . Host and virus genetic factors have also been shown to predispose certain individuals to ACLF due to HBV .…”
Section: Viral Hepatitismentioning
confidence: 99%
“…Patients with HBV flare can succumb to liver failure when there is loss of sufficient liver parenchyma . Multiple extra‐hepatic organ failures can also occur when there is organ damage from the exaggerated inflammation …”
Section: Introductionmentioning
confidence: 99%